Ecology-Driven Real Options: An Investment Framework for Incorporating Uncertainties in the Context of the Natural Environment - Busch, Timo (Journal of business ethics, 2009)
The role of uncertainty within an organization’s environment features prominently in the business ethics and management literature, but how corporate investment decisions should proceed in the face of uncertainties relating to the natural environment is less discussed. From the perspective of ecological economics, the salience of ecology-induced issues challenges management to address new types of uncertainties. These pertain to constraints within the natural environment as well as to institutional action aimed at conserving the natural environment. We derive six areas of ecology-induced uncertainties and propose ecology-driven real options as a conceptual approach for systematically incorporating these uncertainties into strategic management. We combine our results in an integrative investment framework and illustrate its application with the case of carbon constraints.